2017
DOI: 10.1142/s0217751x17500622
|View full text |Cite
|
Sign up to set email alerts
|

Gauge invariant gluon spin operator for spinless nonlinear wave solutions

Abstract: We consider non-linear wave type solutions with intrinsic mass scale parameter and zero spin in a pure SU (2) quantum chromodynamics (QCD). A new stationary solution which can be treated as a system of a static Wu-Yang monopole dressed in off-diagonal gluon field is proposed. A remarkable feature of such a solution is that it possesses a finite energy density everywhere. All considered non-linear wave type solutions have common features: presence of the mass scale parameter, non-vanishing projection of the col… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…First of all, note that a system of separated stationary generalized Wu-Yang monopoles and antimonopoles can not be stable due mutual attraction between the monopole and antimonopole. In addition, despite on the quantum stability of a sinlge stationary spherically symmetric monopole, the solution is rather classically unstable with respect to small axially-symmetric field deformations [14]. This implies that axially-symmetric solutions are more preferable as candidates for the vacuum.…”
Section: Fields [22]mentioning
confidence: 98%
See 1 more Smart Citation
“…First of all, note that a system of separated stationary generalized Wu-Yang monopoles and antimonopoles can not be stable due mutual attraction between the monopole and antimonopole. In addition, despite on the quantum stability of a sinlge stationary spherically symmetric monopole, the solution is rather classically unstable with respect to small axially-symmetric field deformations [14]. This implies that axially-symmetric solutions are more preferable as candidates for the vacuum.…”
Section: Fields [22]mentioning
confidence: 98%
“…Usually one expects that introducing time dependent color fields as vacuum makes worse the vacuum stability since the color electric field leads to an imaginary part of the effective action as well [23]. Surprisingly, it has been found that non-linear plane wave solutions make the problem of vacuum stability more soft, in a sense, that an equation for the unstable modes is very similar to the equation for an electron in the periodic potential [14]. This gives a hint that one can find a proper stationary periodic wave type solution which provides a stable vacuum.…”
Section: Microscopic Quantum Stability Of the Stationary Solutionsmentioning
confidence: 99%
“…Let us first describe the main properties of the stationary spherically symmetric monopole solution [30]. Due to conformal invariance of the Yang-Mills theory the static soliton solutions do not exist in agreement with the known Derrick's theorem.…”
Section: A Stable Spherically Symetric Monopole Field Backgroundmentioning
confidence: 99%
“…Due to conformal invariance of the Yang-Mills theory the static soliton solutions do not exist in agreement with the known Derrick's theorem. It is somewhat unexpected that a pure QCD admits a regular stationary monopole like solution [30]. The solution is described by a simple ansatz which generalizes the static Wu-Yang monopole solution (in spherical coordinates (r, θ, ϕ))…”
Section: A Stable Spherically Symetric Monopole Field Backgroundmentioning
confidence: 99%
See 1 more Smart Citation